Volatilization and partitioning of residual electronic cigarette emissions to particulate matter. Issue 6 (3rd June 2023) - Colby, Henry J.; Katz, Erin F.; DeCarlo, Peter F.
Abstract: The growing prevalence of electronic cigarettes (e-cigs) prompts investigation of their impact on indoor air quality. While the investigation of residual cigarette smoke, also known as third-hand smoke (THS), has been increasing, there is minimal literature on similar residue from e-cig emissions. Lab generated ammonium sulfate aerosol was introduced into a stainless-steel chamber which previously contained JUUL electronic cigarette vape. Aerosol composition was monitored using a high-resolution aerosol mass spectrometer. This was performed in the same chamber 3 times over 5 days. Species from electronic cigarette residue (nicotine and vegetable glycerin) were found to partition to particles with decreasing concentration over the multiple experiments while maintaining a consistent chemical signature. This signature matches closely to that of the primary electronic cigarette vape with notable exclusions of propylene glycol, benzoic acid, and cadmium. Electronic cigarette vape can deposit onto surfaces and act as a long-term source of gas phase nicotine which can concentrate on aerosols and increase human exposure. The chemical processing of vape residue observed here is less substantial than has been previously presented for residual cigarette smoke. While our experiments were performed under controlled conditions, they highlight the importance of understanding indoor electronic cigarette use and unintended routes of exposure. Copyright © 2023 American Association for Aerosol Research